DIVERSITY OF LEARNING: THE BASIS FOR FURTHER INSTRUCTION IN TEACHING MODALITY - Muliani, Muliani; Hidayatullah, Heri (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
This research deals with the diversity of learning as part the development of Interstate New Teachers Assessment and Support Consortium (INTASC Standards) teaching model in teaching Modality. Regarding the use of modalities in English as foreign language for students in Indonesia,it cannot be denied that to most of the students particularly where this research is being carried out,Â  the students awareness of the of modalality limits up to the use of those modal verbs in text ignoring the context. In other words, the ignorance of cultural use occurs in which in contrast, language use must take tense and aspect into consideration. By that reason, the need of teaching modalities further is the main concern as the aim of this research. 80 students of the English Department of IKIP Mataram were involved as the subject of the research where formative assessment were found by applying â€œlearning styleâ€ topic. It was implemented b means of preparing the questionnaire consisting of 1-10 with three-color-box (a,b,c) in which the students were asked to color the box with question mark inside where eventually it was found that the studentsâ€™ diversity can be seen from their hobbies which they use as their learning styles. Most of students love to do sport exercise, watch movie, listening to the music, travelling, reading novel, and singing. Besides, it is also found that students are different in their learning style where some students prefer to learn by discussing, in peer, move around, learn in quite, or even to some of them, any situation things that can distract theirconcentration. In short, it can be concluded that the students are categorized as visual, auditory, and kinesthetic learners.Â 